(untitled) (Comprehensive Journal of Science, 2026)
Libya faces significant challenges in achieving food sovereignty due to its heavy reliance on imports and the limited domestic production of staple cereals such as wheat and barley. This study is significant as it analyzes the national food production gap, identifies factors affecting local production, and provides practical recommendations to enhance food security and national sovereignty. The study employed a descriptive-analytical approach, using official and updated statistical data for the period 2019–2023/2024 on domestic production, national consumption, and imports, alongside a review of relevant literature and previous studies. The results indicate that domestic cereal production covers only about 6–7% of national needs, highlighting a persistent food gap of approximately 3 million tons per year, which renders the country heavily dependent on cereal imports. The study also found that the agricultural sector’s contribution to GDP remains low, and that factors such as water scarcity, climate variability, weak infrastructure, and the absence of strategic planning constitute major constraints on increasing local production and achieving self-sufficiency. Accordingly, the findings suggest that enhancing local cereal production, improving irrigation systems and agricultural infrastructure, supporting small farmers, and diversifying crops represent essential measures to achieve sustainable food sovereignty and reduce import dependence. Based on these results, the study recommends developing a comprehensive national food security strategy that includes improving irrigation systems, supporting small farmers, diversifying crops, and strengthening agricultural policies and infrastructure, thereby ensuring food security, economic stability, and social resilience in Libya.